Intussusception - Acevedo, Alfredo (Cirugía del Uruguay, 1973)
Four cases of intussusception of the nowborn are studied that were seen inthe last ten years. 2 of then ppeasld in the immediate post-operative douse of a pylorectomy for pyloric stenosis. One them !ad a Meckl's diververculum as an etilogy. Another appeared after aente intestinal indigestion and required resection of the intussusception segmen. The importance of early diagnosis is stressed. It must also be stressed the fact of its possible appearence after the medical treatiment of intestinal indigestion.